Hyperoxia-Induced Proliferative Retinopathy: Early Interruption of Retinal Vascular Development with Severe and Irreversible Neurovascular Disruption - Lajko, Michelle (PLoS One, 2016)
Bronchopulmonary dysplasia (BPD) is a major cause of neonatal morbidity in premature infants, occurring as a result of arrested lung development combined with multiple postnatal insults. Infants with BPD exposed to supplemental oxygen are at risk of retinopathy of prematurity as well. Thus, we studied the effects of hyperoxia on the retinal vasculature in a murine model of BPD. The retinal phenotype of this model, which we termed hyperoxia-induced proliferative retinopathy (HIPR), shows severe disruption of retinal vasculature and loss of vascular patterning, disorganized intra-retinal angiogenesis, inflammation and retinal detachment. Neonatal mice were subjected to 75% oxygen exposure from postnatal day (P)0 to P14 to model BPD, then allowed to recover in room air for 1 (P15), 7 (P21), or 14 days (P28). We quantified retinal thickness, protein levels of HIF-1α, NOX2, and VEGF, and examined the cellular locations of these proteins by immunohistochemistry. We examined the retinal blood vessel integrity and inflammatory markers, including macrophages (F4/80) and lymphocytes (CD45R). Compared to controls, normal retinal vascular development was severely disrupted and replaced by a disorganized sheet of intra-retinal angiogenesis in the HIPR mice. At all time-points, HIPR showed persistent hyaloidal vasculature and a significantly thinner central retina compared to controls. HIF-1α protein levels were increased at P15, while VEGF levels continued to increase until P21. Intra-retinal fibrinogen was observed at P21 followed by sub-retinal deposition in at P28. Inflammatory lymphocytes and macrophages were observed at P21 and P28, respectively. This model presents a severe phenotype of disrupted retinal vascular development, intra-retinal angiogenesis inflammation and retinal detachment.